IMPLEMENTASI STRAIGHT LINE METHOD DAN DECLINING BALANCE METHOD PADA PERHITUNGAN PENYUSUTAN AKTIVA TETAP BERBASIS WEB: IMPLEMENTASI STRAIGHT LINE METHOD DAN DECLINING BALANCE METHOD PADA PERHITUNGAN PENYUSUTAN AKTIVA TETAP BERBASIS WEB - Aulia Rahman Hakim Siregar; Raissa Amanda Putri (LPPM Universitas Abdurrab, 2025)
The utilisation of technology in some offices and businesses are still very limited in impacting of the work of an agency effectiveness and efficiency, one of which is calculating assets or fixed assets that are depreciated in companies and agencies to run operations to achieve the objectives of a company or agency. In the practice of calculating depreciation of fixed assets, PDAM Tirtanadi IPAM Limau Manis still has several obstacles in determining the depreciation value for each fixed asset and the systematic implementation of depreciation calculations for all assets, which has several negative implications in the form of inaccuracies in annual budget planning, then difficulty projecting future asset procurement and potential cost overruns due to the absence of accurate depreciation data. The fixed asset depreciation calculations activities was done by web-based include Visual Studio Code, XAMPP, PHP, and MYSQL with the method of the development system used by the method of Research and Development (R&D). Depreciation calculation technique of fixed asset data using the Method of Straight-Line and Declining Balance. The outcome with both methods, the calculation of depreciation was done by a web-based system form that makes it easier for IPAM Limau Manis to provide information of the depreciation calculations of fixed assets which more faster from 2-3 hours manual calculating to 3-15 minutes and more accurate.